Preferensi Konsumen terhadap Parfum Berbasis Minyak Atsiri di Kabupaten Subang, Indonesia - Rohayati Suci Indrianingsih; Rahmi Rahmawati (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This research examined patterns in consumer choices and the socioeconomic factors influencing the choice of essential oil-based perfumes in Subang Regency. Empirical data were collected from 100 participants through structured questionnaires and processed using multivariate regression techniques. Results showed that most respondents preferred unisex scents, 8-hour longevity, spray-type packaging, 50 ml packaging, single-unit packaging, and a price point of IDR 150,000. The findings indicate that demographic attributes such as age, educational attainment, and earnings, expenditures, and number of family members collectively exert a meaningful influence on consumer preference formation within the observed context. A partial analysis shows that only income and the number of family members significantly influence consumer preferences. These findings provide empirical insight into consumer behavior toward essential oil-based perfumes and can serve as a reference for product development and marketing strategy for perfume producers.